Dentist knowledge about dental health management for disabled child at Primary Health Service in Bandung - Nur, Elvanissa Ruslan; Pertiwi, Arlette Suzy Puspa; Susilawati, Sri (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Introduction: Disabled children encounter physical and/or mental hindrance that interferes the normal growth and development. Children with disability have lower oral hygiene level compared to normal children, hence a thorough dental treatment for these children are very important. The Indonesiaâs Health Ministerâs regulation number 89 in 2015 has become one of the references in performing dental treatment for the disabled children. Methods: This study was a descriptive study by using questionnaire to gather the data. Results: This study showed 69,73% of the dentists at Primary Health Service in Bandung were aware of the government regulation about the primary health service for children with disability. Discussion: Preventive and curative efforts are necessary regarding the fact that disabled children have higher level of poor oral hygiene than normal children. The sufficient category shows that the dentists in primary health center need additional information and knowledge to identify the children with disability. Conclusion: The dentist knowledge of the oral health service for children with disability in primary service based on Ministry of Health Republic of Indonesia regulation number 89 in 2015 is sufficient regarding the percentage of 69,73%.